War matters : material culture in the Civil War era - Cashin, Joan E. (North Carolina scholarship online., 2018)
Material objects lie at the crux of understanding individual and social relationships in history, and the Civil War era is no exception. Contributors to this volume argue that an examination of the meaning of material objects can shed new light on the social, economic, and cultural history of the conflict. This text will fundamentally reshape our understanding of the war.